(untitled) (Research, Society and Development, 2020)
The study aims to analyze the concept of communication and language, not limiting them to the verbal and written aspect. Studies of Cognitive Neuroscience and Synergology pointed out in the 1960s that 58% of the communicative process is non-verbal compared to 45% verbal and vocal. Methodology. We adopted for this study a documentary research where articles were searched in the Scielo and PubMed Platform with the keywords - language, verbal and non-verbal communication and neuroscience. However, in order to meet the methodological need to validate the qualitative analysis of this study, we turn to other publications. Discussion. We emphasize, notwithstanding, that the most recent studies by Ramos and Bortagarai in 2011 indicated that non-verbal communication covers about 93% of the possibilities of expression in a context of social interaction. Results. The present study is still limited by the scarcity of publications directed or applied to the theme contemplated by a multidisciplinary and transdisciplinary vision.